3-D structural and functional characterization of the purified KATP channel complex Kir6.2-SUR1. - Mikhailov, M; Campbell, J; De Wet, H; Shimomura, K; Zadek, B; Collins, R; Sansom, MS; Ford, R; Ashcroft, F (2005)
ATP-sensitive potassium (K(ATP)) channels conduct potassium ions across cell membranes and thereby couple cellular energy metabolism to membrane electrical activity. Here, we report the heterologous expression and purification of a functionally active K(ATP) channel complex composed of pore-forming Kir6.2 and regulatory SUR1 subunits, and determination of its structure at 18 A resolution by single-particle electron microscopy. The purified channel shows ATP-ase activity similar to that of ATP-binding cassette proteins related to SUR1, and supports Rb(+) fluxes when reconstituted into liposomes. It has a compact structure, with four SUR1 subunits embracing a central Kir6.2 tetramer in both transmembrane and cytosolic domains. A cleft between adjacent SUR1s provides a route by which ATP may access its binding site on Kir6.2. The nucleotide-binding domains of adjacent SUR1 appear to interact, and form a large docking platform for cytosolic proteins. The structure, in combination with molecular modelling, suggests how SUR1 interacts with Kir6.2.